Capital dredging proceedings of the conference organized by the Institution of Civil Engineers and held in Edinburgh on 15-16 May 1991. (Thomas Telford Ltd, 1991)
The dredging of a completely new site, requires careful investigation of site conditions. This book draws on the experience of a variety of expert authors to explain how to avoid operational problems, high maintenance costs and how to minimise the environmental impact.